2013
DOI: 10.4321/s1130-01082013000400002
|View full text |Cite
|
Sign up to set email alerts
|

Does dermatitis herpetiformis result in bone loss as coeliac disease does?: a cross sectional study

Abstract: Introduction and objectives: coeliac disease (CD) and its cutaneous manifestation, dermatitis herpetiformis are both (DH) glutensensitive diseases. Metabolic bone disease is common among patients with CD, even in asymptomatic forms. Data are scarce about bone density in patients with dermatitis herpetiformis. The aim of our study was to compare bone mineral density (BMD) of celiac and dermatitis herpetiformis patients.Methods: 34 coeliac patients, 53 with dermatitis herpetiformis and 42 healthy controls were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…Occasionally gastrointestinal symptoms also occur, but they are often minor [ 9 , 12 ]. It seems presumable that the increased risk of bone fractures would also be associated with DH, but bone complications in DH have been studied scantily and the results are thus far conflicting [ 13 , 14 , 15 , 16 , 17 ]. The only study focusing on the fracture risk in DH found no increase in risk [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally gastrointestinal symptoms also occur, but they are often minor [ 9 , 12 ]. It seems presumable that the increased risk of bone fractures would also be associated with DH, but bone complications in DH have been studied scantily and the results are thus far conflicting [ 13 , 14 , 15 , 16 , 17 ]. The only study focusing on the fracture risk in DH found no increase in risk [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…And when matched by age and gender to a non-affected population, celiac patients have a 40% greater risk for bone fracture [ 2 ]. Even with a silent or extra-intestinal presentation such as dermatitis herpetiformis or dementia, low bone mass is frequently found [ 3 , 4 , 5 ]. One-third of newly diagnosed cases are over 60 years of age which coincides with a period of an increased risk of falls only worsened by the presence of co-morbidities [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that lumbar spine bone mineral content was significantly lower in patients with DH as compared to healthy controls, but higher than in CD patients. In contrast, bone mineral density at the femoral neck and radius of patients with DH was similar to that of healthy controls, whereas subjects with CD also exhibited a significantly reduced bone density in both these sites (18).…”
mentioning
confidence: 61%
“…The present issue of the Revista Española de Enfermedades Digestivas includes an original paper by Katalin Lorinczy et al highlighting the transcendence of CD and DH beyond the intestinal and skin lesions themselves (18). The study of bone mineralization in adult patients with DH has been scarcely reported in the literature and results have been inconclusive so far -While some authors find no lower bone mineral density among patients with DH (19), nor an increased risk of fractures versus classic celiac individuals (20) despite the presence of intestinal disease, others have reported significant changes in bone mass in patients with DH, similar to the rest of celiacs, in association with poorer nutritional status (21).…”
mentioning
confidence: 99%